2014
DOI: 10.1021/jm5010013
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Nonretinoid Retinol Binding Protein 4 Antagonists for the Potential Treatment of Atrophic Age-Related Macular Degeneration and Stargardt Disease

Abstract: Accumulation of lipofuscin in the retina is associated with pathogenesis of atrophic age-related macular degeneration and Stargardt disease. Lipofuscin bisretinoids (exemplified by N-retinylidene-N-retinylethanolamine) seem to mediate lipofuscin toxicity. Synthesis of lipofuscin bisretinoids depends on the influx of retinol from serum to the retina. Compounds antagonizing the retinol-dependent interaction of retinol-binding protein 4 (RBP4) with transthyretin in the serum would reduce serum RBP4 and retinol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 59 publications
1
80
0
Order By: Relevance
“…These proteins are important for maintaining cell activities and transport functions. Recently, a few studies indicated that increased RBP4 in blood may promote retinal dysfunction [34,36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…These proteins are important for maintaining cell activities and transport functions. Recently, a few studies indicated that increased RBP4 in blood may promote retinal dysfunction [34,36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, anti-T2D therapies that block RBP4 are being developed[25]. However, as RBP4 is the major carrier of serum vitamin A, a thorough understanding of how these therapeutic approaches might affect vitamin A metabolism is essential, as anti-RBP4 therapies can compromise vitamin A status in rodents and humans[3335]. …”
Section: Vitamin a And Type 2 Diabetesmentioning
confidence: 99%
“…3,8 We recently reported our initial efforts in this field, which are based on the hypothesis that reduction of the ocular uptake of serum all- trans retinol (retinol, vitamin A) ( 1 ) (Figure 1) via reduction in circulating levels of serum retinol binding protein 4 (RBP4) can lead to a reduced rate of bisretinoid A2E accumulation in the retina. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, our goal was to develop novel chemical matter with improved drug-like characteristics relative to 3 , and our efforts led to the discovery of the novel bicyclic [3.3.0]-octahydrocyclopenta[ c ]pyrrolo RBP4 antagonist 4 . 9 Analogue 4 possesses a favorable balance of suitable in vitro RBP4 binding (scintillation proximity assay (SPA)) and functional RBP4-TTR interaction antagonist (HTRF) activity with significantly improved HLM stability (100% remaining after a 30 min incubation). Furthermore, 4 possesses good pharmacokinetic (PK) and pharmacodynamic (PD) properties, leading to robust and sustained lowering (>85%) of serum RBP4 levels in both acute and chronic rodent oral dosing studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation